EVALUASI PENERAPAN ASPEK EKOLOGI DALAM PENGELOLAAN HUTAN PRODUKSI LESTARI, PADA PT. PERAWANG SUKSES PERKASA INDUSTRI KABUPATEN KAMPAR RIAU - Albahri Albahri; Aras Mulyadi; Sofyan Husein Siregar (Jurnal Ilmu Lingkungan, 2016)
This study aims to determine how the application of the ecological aspects of the management unit PT. Perawang Sukses Perkasa Industri(PSPI)DistrictLipat Kain that have been certified sustainable plantation management.The research was conductedin Apriland May2014atthe PT. PSPI District Lipat Kain,Kampar, Riau. Application of 6 indicators of ecological aspects by PT. PSPI SFM that have been certified by the Director General of Forestry Enterprises P8 / VI-BPPHH / 2011, general has gone well with the 5 indicators include "good" and 1 indicator still includes "bad". The final value of the ecological aspects of the performance of the total value of all the indicators of the ecological aspects of performance by 93%. Based standards and guidelines for SFM assessment, because there are still a valuable indicator of poor, then the final conclusion of the ecological aspects of performance by PT.PSPI District Lipat Kain still "bad". The results showed that thematurity value oftheverifierin the category"good" in the ecological aspects of the standards and guidelines for SFM assessment the Director General of Forestry Enterprises P. 8/VI-BPPHH/2011, can not guarantee there alization of conservation of the forest environment.